Effects of Different Cutting Styles on Physiological Properties in Fresh-Cut Carrots - Ning Zhou; Sen Ma; Minwei Zhang; Jiayi Wang (Plants, 2024)
With the internationalization of Chinese culture, ready-to-cook Chinese food has become popular. Vegetables in Chinese preparations are usually cut into slices, cubes, and shreds. Carrots, as a typical Chinese side dish, were selected as the model in this work. The polyphenol content, antioxidant capacity, O2−, hydrogen peroxide, malondialdehyde, lignin, antioxidant enzymes, and other enzymes activities were analyzed. The results indicated that these parameters were insignificantly different between three cutting styles. Therefore, metabolomics is further employed. Pathway enrichment indicated that glyceollin II and 6″-malonylgenistin were metabolites particularly expressed in the isoflavonoid biosynthesis pathway; (+)-gallocatechin, trans-chlorogenic acid, and (−)-epiafzelechin were specifically identified in the flavonoid biosynthesis pathway after slicing; and shredding caused the expression of coniferyl aldehyde and eugenol, which were specifically expressed in the phenylpropanoid biosynthesis pathway. These results indicate that different cutting styles do not change the physiological indicators of carrots but induce the expression of specific metabolites.